FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA TBS PETANI SAWIT SWADAYA DI PROVINSI JAMBI - Alamsyah, Zulkifli; Napitupulu, Dompak; Hamid, Ernawati; Yanita, Mirawati; Fauziah, Gina (Universitas Jambi, 2019)
Smallholder plantations play an important role in oil palm development in Jambi Province with a contribution of 70.47 percent to the total area and 57.10 to total palm oil production. Most of the smallholder plantations are self-managed which do not get technical guidance from both the government and the private sector. Therefore various problems are found in independent smallholders, one of which is the discrimination of the price of fresh fruit bunches (FFB) produced by independent smallholders. Price discrimination does not only occur between independent smallholders and plasma farmers, but also occurs between independent smallholders. Data were collected from 240 respondents spread across 12 villages in 3 districts of palm oil production centers. Data were analyzed by quantitative descriptive method and using multiple linear regression analysis models. The results of the study concluded that there were differences in prices around Rp. 300 to Rp. 500 per kg of FFB between prices received by independent smallholders and prices received by plasma farmers and among independent smallholders. The price difference is significantly influenced by the quality factor of the seeds used, the amount of fertilizer use, the experience of farmers in farming and the marketing channels used.